Penyakit Akibat Kerja : Telaah Literatur Terhadap Peran Identifikasi Dini dan Intervensi Kesehatan di Tempat Kerja - Asterlita Ryane Wenas; Firmita Dwiseli (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Occupational diseases continue to pose significant challenges to worker health and productivity worldwide. This integrative literature review analyzes ten selected journal articles from 2019 to 2025 that discuss the role of early detection and workplace health interventions in preventing occupational diseases. Findings reveal that medical surveillance, routine check-ups, and AI-based stress detection technologies are effective tools for identifying health risks at an early stage. Workplace interventions such as ergonomic programs, chemical exposure controls, and community-based health promotion show measurable improvements in worker health and compliance with safety protocols. The Total Worker Health® framework by NIOSH emerges as a comprehensive strategy to integrate health protection and promotion in the workplace. However, implementation gaps remain, particularly in the informal sector, due to limited infrastructure and low awareness. This study concludes that combining early detection with structured health interventions, supported by strong policy and stakeholder involvement, is key to reducing occupational disease burdens.